Optimization of process parameters for boron adsorption from sea water using Moringa oleifera seeds - Jami, Mohammed Saedi; Zakaria, Nur Syahirah; Ahmed, Moussa Mohamed; Ngabura, Mohammed; Ahmad, Mani Malam (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Boron is an essential element for plants, animal and human. Nonetheless, its presence in seawater and some natural ground waters could be harmful to plants and animals. Human life and the eco-system could also be seriously affected when exposed to excess boron. Boron has various applications especially in the industrial sector that led to its easy discharge to the environment. In order to safeguard public health, many separation technologies have been used in boron removal from seawater. Among these technologies, adsorption process is highly recommended because it can treat solutions with very low concentration of boron using selective adsorbents. In this work, Moringa oleifera has been chosen to be adsorbent due to its non-toxic and biodegradable properties and promising removal efficiency. Besides, it is environmentally friendly; it does not significantly affect the pH and conductivity of water after the treatment. Therefore, this study aims to investigate the effect of parameters on the adsorption capacity of M. oleifera. The studied parameters that influenced boron sorption are solution pH (7-9), adsorbent dosage (0.4-0.8 g), and contact time (60-180 min) were optimized by using Face-centred Central Composite Design (FCCCD). The results showed that the highest percentage removal of 65% was achieved at optimum pH of 8, contact time of 120 min and adsorbent dosage of 0.6 g. The adsorption studies were better fitted to Freundlich isotherm compared to Langmuir isotherm model.